PEMBIASAAN SOSIALISASI PADA ANAK SEKOLAH DASAR PASCA PANDEMI COVID-19 DALAM UPAYA PENINGKATAN PENGETAHUAN DAN PERILAKU HIDUP BERSIH DAN SEHAT - Hanis Kusumawati Rahayu; Khairunnida Rahma; Gyta Krisdiana Cahyaningrum; Wahyuni Dwi Cahya (LPPM Universitas Bina Bangsa, 2024)
The COVID-19 pandemic has changed the lifestyle of the community as a whole, including children at the elementary school level. This manuscript aims to evaluate the impact of habituation of Clean and Healthy Living Behavior (PHBS) on elementary school children after the COVID-19 pandemic. This study used observational methods and quantitative data analysis to identify behavioral changes and their impact on children's health